2014
DOI: 10.1016/j.resp.2013.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Role of central and peripheral opiate receptors in the effects of fentanyl on analgesia, ventilation and arterial blood-gas chemistry in conscious rats

Abstract: This study determined the effects of the peripherally restricted µ-opiate receptor (µ-OR) antagonist, naloxone methiodide (NLXmi) on fentanyl (25 µg/kg, i.v.)-induced changes in (1) analgesia, (2) arterial blood gas chemistry (ABG) and alveolar-arterial gradient (A-a gradient), and (3) ventilatory parameters, in conscious rats. The fentanyl-induced increase in analgesia was minimally affected by a 1.5 mg/kg of NLXmi but was attenuated by a 5.0 mg/kg dose. Fentanyl decreased arterial blood pH, pO2 and sO2 and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
126
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(139 citation statements)
references
References 83 publications
13
126
0
Order By: Relevance
“…That morphine elicited an initial increase in fR is consistent with our previous evidence that this opioid initially enhances fR in conscious Sprague-Dawley rats by activation of peripheral μ-ORs (Henderson et al, 2013, 2014). Morphine lowered fR in the HX but not HC group.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…That morphine elicited an initial increase in fR is consistent with our previous evidence that this opioid initially enhances fR in conscious Sprague-Dawley rats by activation of peripheral μ-ORs (Henderson et al, 2013, 2014). Morphine lowered fR in the HX but not HC group.…”
Section: Discussionsupporting
confidence: 91%
“…As was expected (Henderson et al, 2013, 2014; May et al, 2013a), the increases in fR (and concomitant decreases in TI and Te) and Vt, Ve and Vt/Ti (respiratory drive) elicited by the HC and HX challenges were substantially smaller in morphine-treated SHAM rats than in their saline-treated counterparts. However, it was evident that the ventilatory depressant effects of morphine were substantially greater against HC than HX.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Previously, the use of opioids was not allowed for analgesia during labor, but sufentanil is an exception with its positive effect on neonatal outcomes and parturients . However, some studies have found that sufentanil can result in respiratory inhibition to a certain degree, which is not conducive to awake intubation and difficult airways . Dexmedetomidine, a highly selective alpha‐2 adrenergic receptor agonist, is found to cause mild respiratory depression, maintain hemodynamic stability and allow awake intubation and parturients regaining awareness during sedation and analgesia, all of which make it a potential option for anesthesia in obstetrics .…”
Section: Introductionmentioning
confidence: 99%